The Self-Meaning of College Students Use ChatGPT in Social Reality - Dhimas Genta Ramadhan; Eka Yusup (Universitas Dharmawangsa Medan, 2026)
This study aims to analyze and examine the motives, experiences, and meanings of the social phenomenon regarding how students interact with artificial intelligence (ChatGPT), which has not previously been explored in scientific studies within social phenomenology interactions. In the findings of this study, various data reductions were obtained through interviews with 3 informants and 1 expert data using purposive sampling techniques, resulting in several major themes that can be examined. From the perspective of using Alfred Schutz's main phenomenological theory and Peter L. Berger's supporting theory of social reality construction, it was found that the main motive for students choosing to use ChatGPT is based on aspects of the Because of Motive and In Order to Motive, derived from reasons for use and usage purposes, as well as other conceptual aspects such as Life World, Intersubjective, and Stock of Knowledge, and also in the concept within the theory of social reality construction such as Externalization, Objectivation, Internalization, thus the data findings signify that now the process of interaction between students and artificial intelligence is understood as a social reality within the academic space through a collection of meanings and experiences constructed into the lives of students. Now, students feel that their experience in discussing with artificial intelligence like ChatGPT is very helpful, making them more confident and becoming students who innovate in handling lectures as well as other tasks.